Synthesis of deep-cavity fluorous calix[4]arenes as molecular recognition scaffolds - Osipov, Maksim; Chu, Qianli; Geib, Steven J.; Curran, Dennis P.; Weber, Stephen G. (Beilstein Journal of Organic Chemistry, 2008)
Several lower-rim perfluoroalkylated (fluorous) calix[4]arenes have been synthesized by O-alkylation of the parent calix[4]arene. The compounds are formed in the cone conformation. They are soluble in several fluorous solvents and show promise for use in sensing, selective extractions and other applications.
Keywords: calixarene; fluorous; hydrofluoroethers; organofluorine; (perfluoroalkyl)alkyl aryl ethers

Calixarenes Revisited - Gutsche, C. D. (Royal Society of Chemisty, 1998)

(untitled) - Zinke, A.; Ziegler, E. (Ber. Dtsch. Chem. Ges. B, 1944)

(untitled) - Hong, B. H.; Bae, S. C.; Lee, C.-W.; Jeong, S.; Kim, K. S. (Science, 2001)

(untitled) - Orr, G. W.; Barbour, L. J.; Atwood, J. L. (Science, 1999)

(untitled) - Prins, L. J.; De Jong, F.; Timmerman, P.; Reinhoudt, D. N. (Nature, 2000)

(untitled) - Casnati, A.; Barboso, S.; Rouquette, H.; Schwing-Weill, M.-J.; Arnaud-Neu, F.; Dozol, J.-F.; Ungaro, R. (J. Am. Chem. Soc., 2001)

(untitled) - Ballester, P.; Shivanyuk, A.; Far, A. R.; Rebek, J., Jr (J. Am. Chem. Soc., 2002)

(untitled) - Sun, X. H.; Li, W.; Xia, P. F.; Luo, H.-B.; Wei, Y.; Wong, M. S.; Cheng, Y.-K.; Shuang, S. (J. Org. Chem., 2007)

(untitled) - Smirnov, S.; Sidorov, V.; Pinkhassik, E.; Havliček, J.; Stibor, I. (Supramol. Chem., 1997)

Supramolecular Chemistry - Steed, J. W.; Atwood, J. L. (John Wiley & Sons, Inc., 2000)

(untitled) - Arnaud-Neu, F.; Schwing-Weill, M.-J. (Synth. Met., 1997)

(untitled) - Iwamoto, K.; Araki, K.; Shinkai, S. (J. Org. Chem., 1991)

Handbook of Fluorous Chemistry - Gladysz, J. A.; Curran, D. P.; Horváth, I. T. (Wiley-VCH, 2004)

Regular Solutions - Hildebrand, J. H.; Scott, R. L. (Prentice-Hall, 1962)

(untitled) - Sandford, G. (Tetrahedron, 2003)

The Handbook of Fluorous Chemistry - Gladysz, J. A.; Emnet, C. (Fluorous Solvents and Related Media, 2004)

(untitled) - Curran, D. P. (Pure Appl. Chem., 2000)

(untitled) - Chu, Q.; Zhang, W.; Curran, D. P. (Tetrahedron Lett., 2006)

(untitled) - Yang, F.; Newsome, J. J.; Curran, D. P. (J. Am. Chem. Soc., 2006)

(untitled) - Boswell, P. G.; Bühlmann, P. (J. Am. Chem. Soc., 2005)

(untitled) - O’Neal, K. L.; Geib, S.; Weber, S. G. (Anal. Chem., 2007)

(untitled) - Martin, O. M.; Mecozzi, S. (Supramol. Chem., 2005)

(untitled) - Martin, O. M.; Mecozzi, S. (Tetrahedron, 2007)

(untitled) - Martin, O. M.; Yu, L.; Mecozzi, S. (Chem. Commun., 2005)

(untitled) - Buscemi, S.; Pace, A.; Piccionello, A. P.; Pappalardo, S.; Garozzo, D.; Pilati, T.; Gattuso, G.; Pappalardo, A.; Pisagatti, I.; Parisi, M. F. (Tetrahedron Lett., 2006)

(untitled) - Glennon, J. D.; Hutchinson, S.; Harris, S. J.; Walker, A.; McKervey, M. A.; McSweeney, C. C. (Anal. Chem., 1997)

(untitled) - Rathore, R.; Abdelwahed, S. H.; Guzei, I. A. (J. Am. Chem. Soc., 2004)

(untitled) - Matsubara, H.; Yasuda, S.; Sugiyama, H.; Ryu, I.; Fujii, Y.; Kita, K. (Tetrahedron, 2002)

(untitled) - Chu, Q.; Yu, M. S.; Curran, D. P. (Tetrahedron, 2007)

(untitled) - Larsen, M.; Jørgensen, M. (J. Org. Chem., 1997)

(untitled) - Wong, M. S.; Xia, P. F.; Zhang, X. L.; Lo, P. K.; Cheng, Y.-K.; Yeung, K.-T.; Guo, X.; Shuang, S. (J. Org. Chem., 2005)

(untitled) - Mastalerz, M.; Dyker, G.; Flörke, U.; Henkel, G.; Oppel, I. M.; Merz, K. (Eur. J. Org. Chem., 2006)

(untitled) - Scheerder, J.; Vreekamp, R. H.; Engbersen, J. F. J.; Verboom, W.; van Duynhoven, J. P. M.; Reinhoudt, D. N. (J. Org. Chem., 1996)

(untitled) - Cho, Y. L.; Rudkevich, D. M.; Rebek, J., Jr (J. Am. Chem. Soc., 2000)

(untitled) - Wong, M. S.; Zhang, X. L.; Chen, D. Z.; Cheung, W. H. (Chem. Commun., 2003)

(untitled) - Arai, S.; Ohkawa, H.; Ishihara, S.; Shibue, T.; Takeoka, S.; Nishide, H. (Bull. Chem. Soc. Jpn., 2005)

(untitled) - Ohkawa, H.; Arai, S.; Takeoka, S.; Shibue, T.; Nishide, H. (Chem. Lett., 2003)